Game QA and testing : game development essentials. - Levy, Luis, ....-; Novak, Jeannie, 1966- (New York : Delmar Cengage Learning, 2010)
GAME DEVELOPMENT ESSENTIALS: GAME TESTING & QA explains the history of testing, basic and advanced techniques, educational background, and available online resources on testing. With GAME DEVELOPMENT ESSENTIALS: GAME TESTING & QA, dedicated gamers can learn what it takes to become a professional, well-paid QA or production testers ? entering the game industry from the front door. The authors envision a future where game testers are recognized as well-trained, elite professionals that play a crucial role in game development. GAME DEVELOPMENT ESSENTIALS: GAME TESTING & QA is a comprehensive guide to the mysterious game testing profession. Through first-hand experience and deep research, the authors shed light on the history of testing, basic and advanced techniques, job-hunting, and moving up in the ladder of game development. GAME DEVELOPMENT ESSENTIALS: GAME TESTING & QA is the first book of its kind, preparing would-be testers for an exciting career in the game industry.